15(-42x-40)=15(-8x+244)

Simple and best practice solution for 15(-42x-40)=15(-8x+244) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 15(-42x-40)=15(-8x+244) equation:


Simplifying
15(-42x + -40) = 15(-8x + 244)

Reorder the terms:
15(-40 + -42x) = 15(-8x + 244)
(-40 * 15 + -42x * 15) = 15(-8x + 244)
(-600 + -630x) = 15(-8x + 244)

Reorder the terms:
-600 + -630x = 15(244 + -8x)
-600 + -630x = (244 * 15 + -8x * 15)
-600 + -630x = (3660 + -120x)

Solving
-600 + -630x = 3660 + -120x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '120x' to each side of the equation.
-600 + -630x + 120x = 3660 + -120x + 120x

Combine like terms: -630x + 120x = -510x
-600 + -510x = 3660 + -120x + 120x

Combine like terms: -120x + 120x = 0
-600 + -510x = 3660 + 0
-600 + -510x = 3660

Add '600' to each side of the equation.
-600 + 600 + -510x = 3660 + 600

Combine like terms: -600 + 600 = 0
0 + -510x = 3660 + 600
-510x = 3660 + 600

Combine like terms: 3660 + 600 = 4260
-510x = 4260

Divide each side by '-510'.
x = -8.352941176

Simplifying
x = -8.352941176

See similar equations:

| 8x=2-x^2 | | 6(x-7)+3(x+14)+2(x-15)=-9(x-4)+3(x+7) | | 9-6x=-4x+7 | | 4.8+10m=8.53 | | -11-5r=-8(5r-3) | | 31e=102 | | 5x^2+40=30x | | -18=16 | | -11=-45r-3 | | 63x=8p-14 | | 6x-6-3x=x+5+x | | 9a+2b+8a+3b= | | 19z=38 | | 19z=28 | | 5x^2-33x+56=0 | | 7.5+n=9.63 | | 2d-6d=5 | | (1-3x)=4 | | 4(3x+1)+8x=-23-7x | | 7.95-3.86=n | | 8=-5+z | | 7.95+3.86=n | | 6x+8=25-2 | | 5x+8=25-1 | | 2x^3=256 | | -22=2b | | 5x+9=25-2 | | 3x-6+15=41 | | 245-x^2=0 | | 5x+8=25-2 | | 2y+4x+74=180 | | 1-5v=-14 |

Equations solver categories